2019
DOI: 10.7150/jca.29932
|View full text |Cite
|
Sign up to set email alerts
|

The Down-Regulation of SUZ12 Accelerates the Migration and Invasion of Liver Cancer Cells via Activating ERK1/2 Pathway

Abstract: The suppressor of zest 12 (SUZ12), an essential subunit of the transcription polycomb repressive complex 2 (PRC2), has been found to be involved in HBV X-induced oncogenic transformation in hepatocellular carcinoma (HCC). However, the specific function of SUZ12 has not yet been determined in the pathogenesis of migration and invasion of HBV-associated HCC. Here, our results showed that SUZ12 was significantly down-regulated in HBV-related HCC tissues compared with adjacent non-tumor tissues by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It is a component of the PRC2/EED-EZH2 complex, which methylates ‘Lys-9’ (H3K9me) and ‘Lys-27’ (H3K27me) of histone H3, leading to transcriptional repression of the affected target gene [74]. Further, we observed different studies reported SUZ12 for the treatment of hepatocellular carcinoma [75,76]. We have also tried to investigate the therapeutic applications of the identified prognostic markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a component of the PRC2/EED-EZH2 complex, which methylates ‘Lys-9’ (H3K9me) and ‘Lys-27’ (H3K27me) of histone H3, leading to transcriptional repression of the affected target gene [74]. Further, we observed different studies reported SUZ12 for the treatment of hepatocellular carcinoma [75,76]. We have also tried to investigate the therapeutic applications of the identified prognostic markers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the upregulation of SUZ12 was reported to be a prognostic factor for poor prognosis of various malignancies [88,89]. But, in contrast, recently, one of the studies has shown that the lower expression of SUZ12 results in poor prognosis in terms of the 5-year survival of HCC patients [76]. Xue et al, further demonstrated the significant down-regulation of SUZ12 in HBV-related HCC tissue samples in comparison to normal samples; and its overexpression impaired HCC cell’s migration and invasion [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPI analysis revealed those seven miRNAs' target genes with the strongest protein interactions. Moreover, it has been reported that the abnormal expression of RNF2, AGO1, CREBBP, and SUZ12 is closely related to the invasion and metastasis of HCC [ 32 35 ]. These results indicate that MRMs are associated with metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 MMP2 and MMP9 are EMT markers that could be increased significantly during EMT process. 41,42 Therefore, changes in EMT-related gene expressions serve as important markers in indicating the degree of metastasis in tumor cells. In the present research, our results showed that miR-524-5p/FSTL1 could significantly regulate migration and invasion of BC cells.…”
Section: The Role Of Mir-524-5p In Breast Cancermentioning
confidence: 99%